Factors Associated with Home Care Outcomes among Community-Dwelling Older Adult Patients with Dementia - Amal Al Ghassani; Mohammad Rababa (Dementia and Geriatric Cognitive Disorders Extra, 2021)
Background: With the increase in the proportion of people with dementia (PWD), it is necessary to address dementia-related issues among older adults who live at home; however, there is no integrative review on this issue. Objectives: To describe and analyze quantitative and qualitative studies from primary sources in order to identify the factors which impact home care outcomes among PWD. Methods: A computer search of PsycINFO, MEDLINE (PubMed), and the Cumulative Index of Nursing and Allied Health Literature (CINAHL) was performed. This study was guided by Whittemore and Knafl’s integrative review method. Results: This review of the literature identified 3 main factors related to home care outcomes among PWD. These factors are environmental factors, caregiver-related factors, and social network factors. Conclusions: Further research is required to investigate the impacts of multiple social and environmental factors on home care outcomes among PWD; which can eventually be used by nurses and family caregivers when providing care for older adult PWD.